Magnesium vs. machined surfaced titanium - osteoblast and osteoclast differentiation - Kwon, Yong-Dae (The Korean Academy of Prosthodontics, 2014)
PURPOSE: This study focused on in vitro cell differentiation and surface characteristics in a magnesium coated titanium surface implanted on using a plasma ion source. MATERIALS AND METHODS: 40 commercially made pure titanium discs were prepared to produce Ti oxide machined surface (M) and Mg-incorporated Ti oxide machined surface (MM). Surface properties were analyzed using a scanning electron microscopy (SEM). On each surface, alkaline phosphatase (ALP) activity, alizarin red S staining for mineralization of MC3T3-E1 cells, and quantitative analysis of osteoblastic gene expression, were evaluated. Actin ring formation assay and gene expression analysis of TRAP and GAPDH performing RT-PCR were performed to characterize osteoclast differentiation on mouse bone marrow-derived macrophages (BMMs). RESULTS: MM showed similar surface morphology and surface roughness with M, but was slightly smoother after ion implantation at the micron scale. M was more hydrophobic than MM. No significant difference between surfaces on ALP activity at 7 and 14 days were observed. Real-time PCR analyses showed similar levels of mRNA expression of the osteoblast phenotype genes; osteopontin (OPN), osteocalcin (OCN), bone sialoprotein (BSP), and collagen 1 (Col 1) in cell grown on MM at 7, 14 and 21 days. Alizarin red S staining at 21 days showed no significant difference. BMMs differentiation increased in M and MM. Actin ring formation assay and gene expression analysis of TRAP showed osteoclast differentiation to be more active on MM. CONCLUSION: Both M and MM have a good effect on osteoblastic cell differentiation, but MM may speed the bone remodeling process by activating on osteoclast differentiation.